English Language Teachers’ Views on the New National Curriculum for 2nd Graders - Arda ARIKAN (Nalans, 2017)
Prior to the 2014-2015 school year, English language courses used to start at the fourth grade in Turkish primary schools. Starting in the 2014-2015 school year, second graders in Turkish primary schools started to take English language courses with the implementation of the new national curriculum for primary schools’ grades 2 to 8. What made this curriculum different from previous ones was its insistence on curricular gains that were designed in consideration of communicative language teaching and the Common European Framework of Reference for Languages: Learning, teaching, assessment (CEFR). So far, little research has been produced collecting teachers’ views on this new curriculum in practice. Hence, in this study, the views of 4 primary school English language teachers currently teaching second graders were collected and analyzed to understand the perceived strengths and weaknesses of the new curriculum and the educational appropriateness of the curricular gains set for that specific level (2nd grades). Secondly, theoretical concerns and practical challenges associated with the implementation of the new curriculum are studied. Results showed that majority of these teachers had positive views on the new curriculum with its curricular gains although classroom materials and teaching hours remain problematic for them.